Factors associated with suicidal ideation among university students - Hugo Gedeon Barros dos Santos; Samira Reschetti Marcon; Mariano Martínez Espinosa; Makilin Nunes Baptista; Paula Mirianh Cabral de Paulo
ABSTRACT Objective: to analyze the factors associated with suicidal ideation in a representative sample of university students. Methods: cross-sectional study, carried out with 637 students of the Federal University of Mato Grosso. The presence of suicidal ideation, demographic and socioeconomic variables, use of alcohol through the Alcohol, Smoking and Substance Involvement Screening Test, and depressive symptoms (Major Depression Inventory) were investigated. Bivariate analysis was performed with the Chi-square test and multivariate analysis using the Poisson regression model. Results: it was found that 9.9% of the students had suicidal thoughts in the previous 30 days and, in the bivariate analysis, the variables economic class, sexual orientation, religious practice, suicide attempts in the family and among friends, alcohol consumption and depressive symptoms were associated with suicidal ideation. In the multivariate analysis sexual orientation, suicide attempts in the family and the presence of depressive symptoms remained as associated factors. Conclusion: these findings constitute a situational diagnosis that enables the formulation of academic policies and preventive actions to confront this situation on the university campus.